2004
DOI: 10.1007/s00586-004-0743-z
|View full text |Cite
|
Sign up to set email alerts
|

CT evaluation of the pattern of odontoid fractures in the elderly?relationship to upper cervical spine osteoarthritis

Abstract: IntroductionAbove the age of 70 years, fracture of the odontoid process is the most common cervical spine injury [8,9]. Unlike the younger population, in whom odontoid process fractures are caused by high-energy injuries, in the elderly population they are frequently caused by low-energy trauma like falls [8,10]. The classification system detailed by Anderson and D' Alonzo for odontoid process fractures is Abstract Odontoid fractures are common in the elderly following minor falls. Almost all of them have oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 17 publications
2
68
1
1
Order By: Relevance
“…To analyse degenerative changes of the atlantoaxial joints observed in elderly patients or following C2-fractures in younger patients [20,31], all C1-2 joints were scored on transoral odontoid views according to Lakshamanan [44] (Table 3), and the median height of the C1-2 joints was measured. As the study showed difficulties in differentiating the subtypes 0 and 1, as well as type 2 and 3, statistical calculations were performed to stratify a group A (none or mild degenerative changes C1-2, type 0 and 1 [44]) and a group B (advanced degenerative changes C1-2, type 2 and 3 [44]).…”
Section: Methodsmentioning
confidence: 99%
“…To analyse degenerative changes of the atlantoaxial joints observed in elderly patients or following C2-fractures in younger patients [20,31], all C1-2 joints were scored on transoral odontoid views according to Lakshamanan [44] (Table 3), and the median height of the C1-2 joints was measured. As the study showed difficulties in differentiating the subtypes 0 and 1, as well as type 2 and 3, statistical calculations were performed to stratify a group A (none or mild degenerative changes C1-2, type 0 and 1 [44]) and a group B (advanced degenerative changes C1-2, type 2 and 3 [44]).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, CT scans were analysed regarding atlanto-dental osteoarthritis which was defined as narrowed atlanto-dental joint space with osteophytosis [37].…”
Section: Methodsmentioning
confidence: 99%
“…According to the classification of Lakshamanan [54] AAOA was a mean of 1.1 ± 1.0 points (range 0-3) left and 1.0 ± 1.0 points (range 0-3) right at follow-up. Injury AAJH was assessable in 16 patients (45.7%).…”
Section: Atlantoaxial Jointsmentioning
confidence: 98%
“…In addition, the left and right atlantoaxial joint hights (lAAJH and rAAJH) were measured on injury CT-scans, if available, and on all follow-up CT-scans at the center of the lateral C1-2 joints as described [44]. For the purpose of comparative studies, AAJ degeneration was assessed using the classification of Lakshmanan [54] too.…”
Section: Assessment Of Lateral Atlantoaxial Joint Degenerationmentioning
confidence: 99%